The Development Process and The Quality of Questioning Skills Instructional Video for English Teachers at SMA Laboratorium UNDIKSHA Singaraja - I Putu Dipta Priyatna; I.G.A. Lokita Purnamika Utami; Made Hery Santosa; Luh Diah Surya Adnyani (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
The aim of this research is to identify how to develop and how is the quality of a prototype instructional video to help English teachers at SMA Laboratorium Undiksha Singaraja develop their questioning skills in teaching English. This study was a Design and Development research following ADDIE steps: Analysis, Design, Develop, Implementation and evaluation. The study showed that there were four steps to develop the prototype, they were: planning, creating prototype, prototype testing and upgrading the preliminary prototype. Also, the study suggested that the prototype was considered a good instructional video for developing questioning skills. Each evaluator completed a quantitative questionnaire and made qualitative comments. The quantitative analysis scored 98% for content, 93% for media, and 90% from users. Those numbers are categorized as very good product where it does not need any revision. Indeed, qualitative analysis gained some suggestions and comments from the experts where there are some weaknesses in the area of content and media. Though there were some revisions for the prototype, the prototype was considered as a good prototype to be finalized later as a ready-to-use product. Implication for future researcher to develop the prototype to a final product for English teachers’ professional learning is mentioned.